Association between screen time and depressive and anxiety symptoms among Chinese adolescents - Xu, Jue; Duan, Hanmin; Qin, Kang; Liu, Bing (Frontiers in Psychiatry, 2025)
BackgroundAlthough many studies have explored the relationship between screen time and depression and anxiety symptoms, there is still a lack of in-depth research in Chinese adolescents who are stressed and sleep-deprived. This research aims to investigate this link and examine the role of sleep duration as a mediating factor.MethodData were collected from 3,307 students from four districts and counties of Hangzhou, Zhejiang Province, China, using a multi-stage random cluster sampling method and self-administered questionnaires. The study applied linear regression to investigate the relationship between screen time and depression and anxiety symptoms, and mediation analysis to understand how sleep duration might influence this relationship.ResultsIn total, approximately 25.5% of the teenagers had more than 2 hours of screen time (33.56% for electronic devices and 17.46% for television), and the average score was 5.942 ± 0.085 for depression symptoms and 4.521 ± 0.076 for anxiety symptoms. The linear regression analysis showed that longer electronic device use (β=0.601, 95%CI: 0.265 to 0.937) and television usage (β=0.751, 95%CI: 0.346 to 1.156) were positively associated with depression symptoms, and electronic device use was also positively associated with anxiety symptoms (β=0.471, 95%CI:0.159 to 0.784). The study found that sleep duration plays a partial mediating role between screen time and mental disorders. For electronic device use, the effect was -27.50% in depression and -44.01% in anxiety symptoms; for television use, the effect was -42.70% in depression symptoms.LimitationsThe cross-sectional study design could not prove causation.ConclusionsThe association between screen time and depression and anxiety symptoms in adolescents was positive, and sleep duration acted as a mediator.